2006 16th Biennial University/Government/Industry Microelectronics Symposium 2006
DOI: 10.1109/ugim.2006.4286365
|View full text |Cite
|
Sign up to set email alerts
|

Compact Models for the I-V Characteristics of Double Gate and Surround Gate MOSFETs

Abstract: The models presented by Lu and Taur, [1], for lightly doped double gate and surround gate MOSFETs each require numerical solution of a transcendental equation. In this paper we present compact solutions for the equations based on the Lambert function, [2]. These solutions are shown to be accurate compared with exact numerical solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The approximations described in [1] and [15], as well as our proposed enhancement described in the next section, were implemented in Scilab and investigated for accuracy, numerical robustness, and computation expense in terms of CPU time. The investigation was carried out on an AMD Opteron 2.4-GHz Linux-based PC featuring 16-GB RAM.…”
Section: Drawbacks Of Existing Approximationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The approximations described in [1] and [15], as well as our proposed enhancement described in the next section, were implemented in Scilab and investigated for accuracy, numerical robustness, and computation expense in terms of CPU time. The investigation was carried out on an AMD Opteron 2.4-GHz Linux-based PC featuring 16-GB RAM.…”
Section: Drawbacks Of Existing Approximationsmentioning
confidence: 99%
“…it is the lowest bias point at which the approximations discussed in both [15] and [1] work. Table I summarizes the results (the accuracy is shown in Fig.…”
Section: Drawbacks Of Existing Approximationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface potential, channel charge and current models that were obtained in [2][3][4]12] require the solution of a transcendental equation (see equation (22) in Appendix A). In [5,6], this transcendental equation is solved iteratively with very fast convergence for circuit simulation application.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published compact modeling work is focused on symmetric and undoped DG-MOSFET devices (see [2][3][4][5][6][10][11][12][13]), whereas real devices are lightly doped, about 10 15 cm -3 , and asymmetric. In the numerical simulation of [14] it is shown that even a small doping density of 10 15 cm -3 could cause a large shift in the surface potential.…”
Section: Introductionmentioning
confidence: 99%